Gender equity as policy paradigm in the Irish educational policy process - O'Sullivan, Denis (Economic & Social Studies, 1999)
The construct of policy paradigm is used to analyse how the proposition that Irish education is a gendered phenomenon has been conceptualized, communicated, reflected in educational policy and acted upon in practice. Intersubjectivity is conceived as a realm of political action in education and the article seeks to excavate it more comprehensively than its usual ?glossed? treatment in educational policy analysis through the schematisation of the construct of policy paradigm. The gender equity paradigm is analysed in terms of this schematisation highlighting its construction, dominion, systematisation, response to counter interpretations of gendered education and possibilities for change.
Keywords: Gender; Equity; Educational policy; Ireland